2015
DOI: 10.1002/cssc.201500800
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐electrochemical Oxidation of Organic C1 Molecules over WO3 Films in Aqueous Electrolyte: Competition Between Water Oxidation and C1 Oxidation

Abstract: To better understand organic-molecule-assisted photo-electrochemical water splitting, photo-electrochemistry and on-line mass spectrometry measurements are used to investigate the photo-electrochemical oxidation of the C1 molecules methanol, formaldehyde, and formic acid over WO3 film anodes in aqueous solution and its competition with O2 evolution from water oxidation O2 (+) and CO2 (+) ion currents show that water oxidation is strongly suppressed by the organic species. Photo-electro-oxidation of formic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The non-CO ad pathway of formic acid oxidation in an acidic electrolyte has been proposed on a Pt thin-film electrode and a monoclinic WO 3 photoanode by Behm et al, based on the in situ spectro-/ electrochemical and online differential electrochemical mass spectroscopy studies, and it was found that formic acid could be photo-/electrooxidized to CO 2 with a selectivity of as high as 90%. 60,61 To elucidate how the dehydrogenation of methanol on Pt/ BiVO 4 /Bi 2 O 3 is promoted under irradiation is crucial for understanding the photo-/electrocatalysis mechanism. It is well accepted that methanol dehydrogenation in an alkaline environment is strongly promoted by the OH ad on the Pt surface.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The non-CO ad pathway of formic acid oxidation in an acidic electrolyte has been proposed on a Pt thin-film electrode and a monoclinic WO 3 photoanode by Behm et al, based on the in situ spectro-/ electrochemical and online differential electrochemical mass spectroscopy studies, and it was found that formic acid could be photo-/electrooxidized to CO 2 with a selectivity of as high as 90%. 60,61 To elucidate how the dehydrogenation of methanol on Pt/ BiVO 4 /Bi 2 O 3 is promoted under irradiation is crucial for understanding the photo-/electrocatalysis mechanism. It is well accepted that methanol dehydrogenation in an alkaline environment is strongly promoted by the OH ad on the Pt surface.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Also, they found the formaldehyde as the incomplete oxidation product prevails for the methanol oxidation. [ 94 ]…”
Section: Photoelectrocatalysis Mechanismmentioning
confidence: 99%
“…Also, they found the formaldehyde as the incomplete oxidation product prevails for the methanol oxidation. [94] WO 3 , TiO 2 , SnO 2 , and so on have also been proposed as one of the components in electrocatalysts to alleviate the "notorious" CO ads poisoning to the Pt catalysts. The intrinsic cause was tentatively ascribed to the strong metal and support (metal oxides) interaction (SMSI) effect between oxides and Pt, which leads to a weakened adsorption of CO ads on Pt surface.…”
Section: Photoelectrocatalysis Mechanismmentioning
confidence: 99%
“…Of course, like all simple C 1 and C 2 compounds and -anions photoelectrochemical as well as electrochemical transformations of HCOOH were investigated before (e.g. Reichert et al [8] and quotations in this paper), with a focus on fuel-cell use of formic acid (Okamoto et al [7]). It turned out that neat HCOOH cannot be oxidized at Pt anodes without some water being present (ibid.…”
Section: Theoretical Considerationsmentioning
confidence: 99%